Anthracofibrosis attributed to mixed mineral dust exposure: report of three cases. Issue 7 (27th June 2008) - Naccache, J-M; Monnet, I; Nunes, H; Billon-Galland, M-A; Pairon, J-C; Guillon, F; Valeyre, D
Abstract : Anthracofibrosis, defined as bronchial luminal narrowing with black pigmentation of the overlying mucosa, has been attributed to tuberculosis. Three patients with anthracofibrosis without mycobacterial infection are described who had previous occupational exposure to mixed dusts. CT scans showed calcified hilar lymph nodes in two patients. Surgical biopsy in one patient and autopsy in another revealed fibrotic lymph nodes with black pigmentation. Mineralogical analysis by transmission electron microscopy of pulmonary, hilar and/or bronchial samples found high levels of particle retention, raised percentages of free crystalline silica and mica in two patients, and free crystalline silica, kaolin and other silicates in the third. No evidence of any other contributory factor was found, suggesting that mixed mineral dust was the most probable cause. These observations suggest that exposure to mixed mineral dust should be added to the aetiology of anthracofibrosis.